The chromosomes and the mitogenome of Ceratitis fasciventris (Diptera: Tephritidae): two genetic approaches towards the Ceratitis FAR species complex resolution - Elena Drosopoulou (Nature Portfolio, 2017)
Abstract Ceratitis fasciventris is a serious agricultural pest of the Tephritidae family that belongs to the African Ceratitis FAR species complex. Species limits within the FAR complex are obscure and multidisciplinary approaches have attempted to resolve phylogenetic relationships among its members. These studies support the existence of at least three additional species in the complex, C. anonnae, C. rosa and C. quilicii, while they indicate the presence of two structured populations (F1 and F2) within the C. fasciventris species. In the present study we present the mitotic karyotype, polytene chromosome maps, in situ hybridization data and the complete mitochondrial genome sequence of an F2 population of C. fasciventris. This is the first polytene chromosome map and complete mitogenome of a member of the FAR complex and only the second reported for the Ceratitis genus. Both polytene chromosomes and mitochondrial sequence could provide valuable information and be used as reference for comparative analysis among the members of the complex towards the clarification of their phylogenetic relationships.